The Everlasting Kingdom: The Kingdom of God in Scripture and in Our Lives - Ferguson, Everett (Way of Life Series, 1989)
This is a small bible study on the use of the word "kingdom" in the Bible. It was in a series called the Way of Life Series and designed for church study. It begins in the Old Testament and moves through to Revelation offering a summary of what the Bible means by the reign of God.